(untitled) (Communications in Computational Physics, 2024)
In this paper, we revisit some nonoverlapping domain decomposition methods for solving diffusion problems with discontinuous coefficients. We discover some interesting phenomena, that is, the Dirichlet-Neumann algorithm and Robin-Robin algorithms may make full use of the ratio of coefficients in some special cases. Detailedly, in the case of two subdomains, we find that their convergence rates are O(ν_1/ν_2) if ν_1 < ν_2, where ν_1, ν_2 are coefficients of two subdomains. Moreover, in the case of many subdomains with red-black partition, the condition number bounds of Dirichlet-Neumann algorithm and Robin-Robin algorithm are 1+ε(1+log(H/h))^2 and C+ε(1+ log(H/h))^2, respectively, where ε equals min{ν_R/ν_B,ν_B/ν_R} and ν_R,ν_B are the coefficients of red and black domains. By contrast, Neumann-Neumann algorithm and Dirichlet-Dirichlet algorithm could not obtain such good convergence results in these cases. Finally, numerical experiments are preformed to confirm our findings.